Cadmium exposure as a key risk factor for residents in a world large-scale barite mining district, southwestern China. (April 2021) - Lu, Qinhui; Xu, Zhidong; Xu, Xiaohang; Liu, Lin; Liang, Longchao; Chen, Zhuo; Dong, Xian; Li, Chan; Qiu, Guangle
Abstract: Cadmium (Cd) contamination is easily generated during the mining and manufacturing of barium (Ba). In this study, concentrations of both Ba and Cd in rice, vegetables, pork, fish, drinking water, and soil samples from an active barite mining district were determined. Daily intakes of Ba and Cd, as well as corresponding health risks, were evaluated. The average total daily exposure doses of Cd were 0.0035 and 0.0012 mg/kg BW/day (geometric mean) in the mining zone (MZ) and the chemical plant zone (PZ), respectively. These values significantly exceed the provisional tolerable monthly intake (25 μg/kg BW/month, equal to 0.00083 mg/kg BW/day). Based on the daily exposure doses, vegetable consumption was the most significant Ba exposure route for residents, contributing around 66.1% of the total exposure. In contrast, rice consumption was the major Cd exposure pathway, accounting for about 85.6% of the total exposure. Although the geometric mean (0.17) and 95th percentile (P95, 0.75) of the total hazard quotient ( HQ ) for Ba were below the acceptable level (1), suggesting that there were no significant health effects caused by Ba exposure, Cd exposure was associated with significant health risks, with the geometric mean of the HQ (1.7) and the P95 (21) well above the acceptable limit (1), indicating the unacceptable non-carcinogenic risk of Cd exposure. In summary, high Cd exposure risk, rather than Ba, was observed for populations living in a large-scale active Ba mining area. Graphical abstract: Image 1 Highlights: Exposure risks of coexisting Ba and Cd from multiple exposure pathways at an active Ba mine were evaluated. The major pathway for human exposure to Ba was from consumption of vegetables, and that for Cd was from consumption of rice. There were unacceptable non-cancer risks to residents from Cd rather than Ba.